A short guide to facilitating risk management : engaging people to identify, own and manage risk - Pullan, Penny; Murray-Webster, Ruth; Randle, Vaneesa (Short guides to business risk, 2011)
A Short Guide to Facilitating Risk Management is for all those who need to make sound decisions in important but risky situations; people who work with groups to identify,prioritize and respond to risks, and who wish to deliver value. The authors provide readable and practical advice in terms of avoiding pitfalls, understanding risk management and the role of facilitator. They include guidance for running workshops, and working with small groups and individuals